The role of play in shaping early childhood character: A systematic literature review - Didi Suryadi; Zsolt Németh; Julian Dewantara; Muhammad Daffa Haidar; Nur Khozanah Ilmah (Khatulistwa Education Center, 2025)
Background. Early childhood character development plays a crucial role in the educational process. However, in practice, it is often overlooked. The concept of